Web Media in Combined Guided Inquiry Learning Lesson Study on Creative Thinking and Student Learning Outcomes - Matondang, Silvia Elastari (UIN Syekh Ali Hasan Ahmad Addary Padangsidimpuan, 2024)
This research aims to determine the creative thinking skills of students who are taught using web media, guided inquiry learning combined with lesson study, which is higher than without using web media. And knowing that the learning outcomes of students taught in guided inquiry learning combined with lesson study using web media are higher than without using web media. The research population was students of class XI Science High School. The sampling technique was simple random sampling consisting of two classes, namely experimental and control with a total sample size of 76 students. This research instrument is a creative thinking test and student learning outcomes. Data analysis techniques are carried out by calculating the level of concept understanding, testing data homogeneity, normality testing and hypothesis testing. The results of the research show that the learning outcomes and creative thinking of students taught in combination lesson study inquiry learning using web media with an average gain of 0.71 and an average of 75.46 compared to without using web media with an average of 0.60 and 55. .20 with significance (0.00 0.05).